Herding Behavior, Overconfidence, Regret Aversion Bias On Investment Decisions - Lilian S Loppies; Maria J.F Maria J.F Esomar1; Innayah Nurulita Janah (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The aim of this study is to examine the effect of herding behavior, overconfidence, regret aversion bias on the investment decisions of PT. Phintraco Sekuritas Ambon Branch. This study used quantitative research methods. The sample used is 30 investors of PT. Phintraco Sekuritas Ambon Branch. A questionnaire with tested results was used as the data collection technique in this study. Based on the results of the study it can be concluded that 1). Herding behavior has no effect and is not significant on investors' investment decisions as shown by the results of the regression analysis indicating that tcount of herding behavior is 1,685 with a significance of 0.104 (not significant). 2). Overconfidence has an effect and is significant on investment decisions3) Regret aversion bias has no effect and is not significant on investors' investment decisions.